The role of community policing in the prevention of farmers suicides: a study of Dharwad district - Sangalad, Purnanand Nagappa (International Multidisciplinary Research Journal, 2012)
Agriculture has always been celebrated as the primary and predominant sector in the Indian economy. True to this, close to 70 percent of the people still depend on agriculture and allied activities for their livelihood. The major portion of Indian farming is dependent on natural rain fall. The rainfall in India is unpredictable. Failure of rains results failure of crops, as a result the farming community falls in the debt trap and the farmers who fail to overcome these problems has taken an extreme step of ending their life. In the present paper an effort is made to discuss the role of community police in the prevention of suicides among farmers. In the community policing there is involvement of citizens in crime prevention process. Various suggestions like educating the farmers on the values of life and properties, about the facilities available to them, designing a model program for prevention of farmerâ€™s suicides Etc., have been discussed in the present paper.Â 